Protozoários ciliados no rúmen de bovinos Nelore e Cruzados Nelore x Europeu sob diferentes sistemas de alimentação - Reis, Cândida Camila dos (2015)
The aim of this study was to identify and quantify the rumen ciliated protozoa of two genetic groups cattle (Nellore and crossbred Nellore x European) under three feeding systems (confined, pasture and pasture with supplement). The rumen fluid samples were obtained from the center of the rumen mass, after … The quantification was done in Sedgewick-Rafter counting chambre in light microscopy. It was determined the content of dry matter (DM), mineral matter (MM), ether extract (EE), crude protein (CP), neutral detergent fiber (NDF) and acid detergent fiber (ADF) to determine the chemical quality of the feed supplied to the animals. The data were submitted to analysis by Generalized Linear Models methodology, assuming Poisson distribution with logarithmic link function, with significance level of 1%. In addition, data were submitted to principal component analysis. The first two principal components were analyzed by least squares. There was a significant interaction (P<0.001) for diets and analyzed races. Occurrence of 14 ciliate genera was observed, being Entodinium the predominant in all animals analyzed. The ciliates belonging to order Entodiniomorphida, Eodinium, Epidinium, Eremoplastron, Eudiplodinium, Metadinium e Ostracodinium had a higher prevalence in Nellore cattle, compared with the racial group crossbred Nellore x European. Protozoa of the family Isotrichidae (Dasytricha e Isotricha) were observed in greater quantities in animals to pasture and pasture with supplement. Regarding the type of food, animals on pasture had higher ciliates density compared to confined animals and pasture with supplement. Occurrence of gender Buestchlia only one animal (prevalence 1,66%), which is one of the few records of this kind in ruminants.